2007
DOI: 10.1590/s1519-69842007000300015
|View full text |Cite
|
Sign up to set email alerts
|

Macroinvertebrate fauna associated with Pistia stratiotes and Nymphoides indica in subtropical lakes (south Brazil)

Abstract: This study was carried out at the Biguás and Polegar lakes, both small environments but at different successional stages. The main objective was to characterize the macroinvertebrate community associated to the aquatic macrophyte stand in each lake in order for this community, the environmental conditions and their water quality to interact. The samples were taken in 2003. The abiotic variables of N and P totals, the temperature, electrical conductivity, pH and dissolved oxygen, as well as the determined cloro… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
3
2

Citation Types

3
22
1
4

Year Published

2012
2012
2024
2024

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 35 publications
(30 citation statements)
references
References 17 publications
3
22
1
4
Order By: Relevance
“…These results can mostly be explained by macrophytes habitat and morphology present in this shallow reservoir, which both macrophytes are floating perennial aquatic plant or free-floating perennial or annual macrophytes. The number of planktonic taxa found was higher than those pointed by Albertoni et al (2007) and lower than found by Onsem et al (2010).…”
Section: Discussioncontrasting
confidence: 66%
See 1 more Smart Citation
“…These results can mostly be explained by macrophytes habitat and morphology present in this shallow reservoir, which both macrophytes are floating perennial aquatic plant or free-floating perennial or annual macrophytes. The number of planktonic taxa found was higher than those pointed by Albertoni et al (2007) and lower than found by Onsem et al (2010).…”
Section: Discussioncontrasting
confidence: 66%
“…The macrophytes stands support epiphytic algae and animals as well as a variety of associated mobile animals, including zooplankton, macrofauna and fish (Albertoni et al, 2007;Christie et al, 2009). Macrophytes provide habitat and refuge for zooplanktonic filter feeders to maintain topdown control on the phytoplankton (Sandilands and Hann, 1997).…”
Section: Introductionmentioning
confidence: 99%
“…On the other hand, the three species of Ensifera that were registered were described as the insects that inhabit moist places and those near to the water: Phlugis sp., Conocephalus sp., and Scudderia sp. The crickets collected in this study were cited by other authors as being a part of the insect community living on floating aquatic plants (Carbonell 1980;Albertoni et al 2007). …”
Section: Discussionmentioning
confidence: 95%
“…These studies provide data on the species diet spectrum, considering that the environments with different physiognomies host different types of potential preys (Ricklefs 2003). The coastal plain of Rio Grande do Sul State, southern Brazil is hydrologically characterized by the existence of shallow freshwater ecosystems such as streams, lagoons and wetlands (Vieira and Rangel, 1988;Albertoni et al 2007). In addition to these natural water bodies, artificial systems represented by the drainage channels and anthropogenic shallow lakes are also present in the region.…”
Section: Introductionmentioning
confidence: 99%
“…In addition to these natural water bodies, artificial systems represented by the drainage channels and anthropogenic shallow lakes are also present in the region. Channels built for the drainage and pluvial water flow are common in the coastal cities of Rio Grande do Sul State (Albertoni and Palma-Silva 2006) while a set of anthropogenic shallow lakes are present in an urban area in the city of Rio Grande (Votto et al 2006;Albertoni et al 2007). The objective of the present work was to study the diet of L. longicaudis in three distinct limnic systems in southern Rio Grande do Sul State, aiming on an approximation about the diet spectrum of the species in this region.…”
Section: Introductionmentioning
confidence: 99%